Chagas' Disease and HIV Co-infection: Genotypic Characterization of the Trypanosoma cruzi Strain - Pacheco Raquel S; Ferreira Marcelo S; Machado Maria Inês; Brito Célia MM; Pires Marize Q; Da-Cruz Alda M; Coutinho Sérgio G (Memorias do Instituto Oswaldo Cruz, 1998)
In the past few years, new aspects of the immunopathology of Chagas' disease have been described in immunosuppressed patients, such as fatal central nervous system lesions related to the reactivation of the parasite. This article is the first description of the genotypic characterization, at the strain level, of Trypanosoma cruzi isolated from a patient with Chagas` disease/AIDS co-infection. The presence of four hypodense lesions was observed in the cranial compute tomographic scan. The diagnosis of AIDS was assessed by the detection of anti-HIV antibodies using enzyme-linked immunosorbent assay (ELISA) and Western blot techniques. The CD4+ lymphocyte counts were maintained under 200 cells/mm3 during one year demonstrating the severity of the state of immunosuppression. Chagas' disease was confirmed by serological and parasitological methods. Trypomastigote forms were visualized in a thick blood smear. The parasite isolated is genotypically similar to the CL strain. The paper reinforces that cerebral Chagas' disease can be considered as another potential opportunistic infection in AIDS resulting from the reactivation of a dormant T. cruzi infection acquired years earlier.